Islamic Populism and Symbolic Convergence in the 2019 Presidential Election - Muhtar, Saepudin; Burhanuddin, Jajat; Munhanif, Ali; Heryanto, Gun Gun (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
This research reveals that both candidates in the 2019 Presidential Election engaged in Islamic populist movements in an attempt to garner sympathy and increase their respective electability. The symbolic convergence of Prabowo's campaign is evident in the institutional nature of the fantasy theme woven by his team, with actions that signify the fundamentalism of Prabowo's camp. In contrast, the fantasy theme constructed by Jokowi's team is notably moderate, as exemplified by the phrase